Evaluation of equilibrium isotherm models for the adsorption of Cu and Ni from wastewater on bentonite clay - Al-Jlil, Saad A. (Materiali in tehnologije, 2013)
A study was carried out to evaluate equilibrium isotherm models for the adsorption of Cu and Ni on bentonite clay from wastewater. The adsorption of Cu and Ni increased with an increase in the pH and was high at the pH values of around 7. The adsorption capacity of bentonite clay increased with an increase in the temperature. The maximum adsorption capacity of bentonite clay was 11.12 mg gsup{-1} and 6.78 mg gsup{-1} for Cu and Ni, respectively at 20 °C. Among the three equilibrium isotherm models used, the Langmuir-Freundlich isotherm model described the experimental data well at different temperatures.
Keywords: adsorpcija; izoterme; baker; nikelj; bentonit; odpadne vode